2014
DOI: 10.2478/sjph-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Population based self-reported acute gastrointestinal infection in slovenia: multiplier study

Abstract: Background: The assessment of the incidence of acute gastrintestinal infections (AGI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Leichte bis moderate Verläufe gastrointestinaler Infekte, insbesondere bei Erwachsenen, werden oftmals nicht gemeldet [51]. Dafür sprechen auch die Ergebnisse internationaler Studien [52][53][54][55]…”
Section: Gastrointestinale Infektionenunclassified
“…Leichte bis moderate Verläufe gastrointestinaler Infekte, insbesondere bei Erwachsenen, werden oftmals nicht gemeldet [51]. Dafür sprechen auch die Ergebnisse internationaler Studien [52][53][54][55]…”
Section: Gastrointestinale Infektionenunclassified
“…Acute gastroenteritis (AG), manifesting with signs and symptoms of diarrhoea, vomiting, abdominal pain or cramps, fever, dehydration, nausea and/or loss of appetite, is usually self-limiting, but leads to a considerable burden of disease, health system use and socio-economic impact. Studies in several European countries estimated the incidence of AG at 0.3–1.5 episodes per person and year [ 1 14 ]. Furthermore, it was found that a considerable 11% of patients with infectious enteritis develop post-infectious irritable bowel syndrome [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of AG for Switzerland is assumed to be comparable, but data is limited to notifiable pathogens reported to the Federal Office of Public Health (FOPH) based on the Epidemics Act. Several studies from other European countries have shown that (i) only 6.4–37.8% of all AG episodes lead to consultation of a physician [ 1 9 , 11 , 12 , 14 ], and (ii) 0.2–1.8% of episodes are reported to national surveillance systems [ 1 , 11 , 14 ]. These proportions are highly variable between countries and pathogens due to different help seeking behaviour, case management and surveillance systems [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The burden of AGI among population of Slovenia is quite high. The cross sectional study should be repeated and laboratory analysis of acute AGI cases added to get a better insight of epidemiological situation ( 4 ).…”
Section: Introductionmentioning
confidence: 99%